Aplikasi E-Learning Siswa Smk Berbasis Web - Marlina, Marlina; Masnur, Masnur; Muh. Dirga.F (Jurnal Sintaks Logika, 2021)
The purpose of writing this thesis is to analyze the system and design a web-based E-Learning application for vocational students to be able to assist in the process of teaching and learning activities. With this application, it is expected to be able to help problems faced by teachers and students outside of class hours, such as lack of communication time between teacher and students, search for information about the material being taught, and of course to facilitate teachers in delivering material to students. The results achieved are the availability of applications supporting teaching and learning activities that can be obtained without being bound by time and place. The conclusion with the existence of web-based E-Learning is to facilitate teacher and student communication, provision of material, ease of assignment and assignment of assignments, as well as facilitate the informational value.